Financial Liberalisation and Small Medium Scale Enterprises Growth in Nigeria (2016)
This paper examined the relationship between financial liberalization and the growth of Small and Medium Scale Enterprises (SMEs) in Nigeria controlling for some other key macroeconomic variables such as investment, inflation and the domestic national output (GDP). Using annual data covering the period 1981-2012, we estimated the effect of the macroeconomic variables on the growth of SMEs. An index which measured the gradual progression and institutional changes involved in financial liberalization was constructed for this study. A number of interesting results were obtained. First, unlike previous studies which concluded that financial liberalization leads to a reduction in financing constraint of SMEs thereby leading to their growth; our results showed that financial liberalization had negative though non-significant effect on the growth of SMEs in Nigeria. Second, the results also showed that inflation had a positive and significant effect on the growth of SMEs in Nigeria. Investment had a positive though non-significant effect on the growth of SMEs in Nigeria. Finally, GDP had a large negative but significant effect on the growth of SMEs. On the basis of the result obtained from the study, government policies towards further liberalization of the financial sector of the country might not lead to an increase in the growth of SMEs given the existence of a negative relationship between SMEs growth and financial liberalization.